HUBUNGAN PENGETAHUAN TERHADAP KOMPETENSI MAHASIWA PROFESI NERS DALAM PENERAPAN EVIDENCE BASED PRACTICE - Hasniatisari Harun; Yusshy Kurnia Herliani; Anita Setyawati (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2018)
Professional nurses could be prepared through professional nursing programs. Professional nursing program is part of the nursing education program. One of the competencies required to be professional nurses is implementing evidence-based practice (EBP) to explore the best nursing interventions for patients to get optimal outcome. Nursing students have learned EBP during bachelor degree by analysis case using the EBP method. However, evaluation related students' understanding of the method and its application of EBP to the clinical practice was none. The purpose of this study was to determine the relationship of knowledge with student competency in the implementation of evidence based practice (EBP) to managed patients in the medical surgical nursing stage. This research is quantitative research. The sample in this study was 120 nursing students who were at professional nursing program that were recruited using total sampling technique. The instrument used is the Evidence Based Practice Questionnaire (EBPQ) questionnaire. The results showed that more than half of the respondents had high knowledge (68%), and high competence (49%). This study shows a meaningful relationship between knowledge of student competence in applying EBP (r = .6070, p <0.01). The findings of this study are important for recommendations related to developing teaching materials in nursing education related to for providing the best service for patients.